Ungdomslitteratur former(er) sig - Henkel, Ayoe Quist (Passage - Tidsskrift for litteratur og kritik, 2016)
“Young Adult Literature in Transformation” Through a media attentive analysis of the novel Akavet by Ronnie Andersen (2014) and brief discussions of other popular novels for and about young adults, this article examines the way young adult literature develops in dialogue with digital and media-based impulses and the consequences this development may have for the predication of youth and the aesthetics and possible characteristics of young adult literature. The article is based on a materiality approach especially inspired by N. Katherine Hayles which has not previously been given attention in the reading of young adult literature or in discussions of possible characteristics of young adult literature. It also includes a discussion of and a variation of Hayles’ triad of form, content and medium, and it assigns a special role to the reader’s articulation inasmuch as Akavet entails a denaturalization of the reading process. From this basis it discusses the classic assumption that young adult literature is about young people’s development process from childhood to adulthood, outlining a passage characterized by linearity, maturity and growth. The article concludes that some young adult literature is realized on yet other premises and that Akavet can be seen as an exponent for a movement from young adult literature as stories of coming-of-age to stories of being-in-age.